Comparisons between conventional, ultrasound-assisted and microwave-assisted methods for extraction of anthraquinones from Heterophyllaea pustulata Hook f. (Rubiaceae) - Barrera Vazquez, Maria Fernanda (2014)
This work reports a comparative study about extraction methods used to obtain anthraquinones (AQs) from stems and leaves of Heterophyllae pustulata Hook (Rubiáceae). One of the conventional procedures used to extract these metabolites from a vegetable matrix is by successive Soxhlet extractions with solvents of increasing polarity: starting with hexane to eliminate chlorophylls and fatty components, following by benzene and finally ethyl acetate. However, this technique shows a low extraction yield of total AQs, and consumes large quantities of solvent and time. Ultrasoundassisted extraction (UAE) and microwave-assisted extraction (MAE) have been investigated as alternative methods to extract these compounds, using the same sequence of solvents. It was found that UAE increases the extraction yield of total AQs and reduces the time and amount of solvent used. Nevertheless, the combination UAE with benzene, plus MAE with ethyl acetate at a constant power of 900W showed the best results. A higher yield of total AQs was obtained in less time and using the same amount of solvent that UAE. The optimal conditions for this latter procedure were UAE with benzene at 50ºC during 60 minutes, followed by MAE at 900W during 15 min using ethyl acetate as extraction solvent.